The economic efficiency of coffee growers in the department of Caldas, Colombia - Hugo Mauricio Salazar Echeverry; Hernando Duque Orrego; Juan Carlos Granobles-Torres (Economies, 2023)
This work evaluates the economic efficiency of coffee growers and the decision-making processes in the configuration of their production systems and agronomic practices over time. For these purposes, information from 136 coffee growers in the department of Caldas was analyzed. These growers systematically recorded and constructed their production costs for seven years (2015- 2021) within the framework of the Business Management Program of the Departmental Committee of Coffee Growers of Caldas. Additionally, through a survey, more information on the socioeconomic types, production systems, and decision-making processes in the implementation of practices and use of technologies was obtained. Stochastic frontier analysis demonstrates that on average, these coffee farmers had an economic efficiency of 89%. The group of coffee growers with efficiency levels equal to or higher than 90% comprised 80 producers (59%). These results indicate that for the period of analysis, there are no structural inefficiencies that cannot be corrected; that is, these coffee growers can increase their efficiency and productivity levels with the available technologies.
Keywords: 330; technical efficiency; productivity; coffee; technical change